Planned Nursing Care - A Main Element of Health Care Management for Ischemic Stroke Patients - Meglena Balaburova; Makreta Draganova (Journal of Biomedical & Clinical Research, 2020)
Morbidity and mortality rate for stroke and ischemic stroke (IS), in particular, have ranked Bulgaria at a top place in the European Union. In the acute recovery stage of the disease, patients need continuous and personalized health care. The assessment of individual needs and adequate planning for nursing interventions, known as nursing process stages, are the basis of effective care management for patients, surviving ischemic stroke (PSIS). Therefore, the study and application of the nursing process in practice have proved to be an objective prerequisite for improving the quality and development of nursing care for PSIS. The objective of the study was to analyze the opinion of nurses working in clinics/departments of Neurology and Physiotherapy and Rehabilitation in three towns in Northern Bulgaria, on health care (HC) planning for PSIS and the required documentation. A direct anonymous inquiry was carried out, using specially designed questions to investigate the opinion of the respondents on the problems studied. Of the 81 individuals approached, 75 (93%) responded. Of these, 52 (69%) were familiar with the main points of the nursing plan concept, and 34 (65%) had heard about the concept during their basic training in the speciality. According to 67 (89%) of the respondents, a care plan was necessary to increase the health care (HC) efficiency in IS patients. Our results showed that healthcare professionals considered care planning an important tool to ensure continuity, evaluation and control of the care provided. According to the respondents, documenting health care and evaluating the activities performed will contribute to improve the quality of nursing care and promote research into nursing care.